从“丰嘉”的形成看翻译的社会属性 = A study on the transformation of Singapore's colloquial place name "Hong Kah" and its social function - 许美玲 Xu, Shirlynn MeiLing (2014)
本文将从新加坡地名“丰嘉”的形成看翻译的社会属性。Hong Kah 是由“奉教”的潮州读音对译而成的，Hong Kah Village 的中文名称在1960 年前被翻译成奉教村。不过，因为“奉教”具有宗教色彩，所以分别在 1960 年代以及 1967 年代，通过 Hong Kah Village 进行了两次英译中的改译活动。文章将结合目的论以及文化导向的翻译研究来探讨翻译与社会文化之间的关系，并且分析译者究竟采用了什么翻译策略和技巧来进行地方名称的翻译，以便顺应新加坡多元种族以及多元文化的社会背景和文化语境。This paper aims to examine the transformation of Singapore's colloquial place name "Hong Kah" and its social function. Hong Kah was initially transliterated according to the pronunciation of its Chinese dialect name. Before 1960s, Hong Kah Village’s Chinese translated name portrayed too much of the religious symbolism in it. Therefore, Hong Kah Village went through two retranslation processes in 1960s and 1970s respectively. In conjunction of both Skopos theory and cultural studies-oriented translation, this paper also explores how the social and cultural aspects influenced the translator’s choice of words and translation techniques used in the targeted text, in order to accommodate to the multi-ethnic and multicultural society in Singapore.